2022
DOI: 10.1111/tpj.15963
|View full text |Cite
|
Sign up to set email alerts
|

A conserved HSF:miR169:NF‐YA loop involved in tomato and Arabidopsis heat stress tolerance

Abstract: Heat stress transcription factors (HSFs) and microRNAs (miRNAs) regulate different stress and developmental networks in plants. Regulatory feedback mechanisms are at the basis of these networks. Here, we report that plants improve their heat stress tolerance through HSF-mediated transcriptional regulation of MIR169 and post-transcriptional regulation of Nuclear Factor-YA (NF-YA) transcription factors. We show that HSFs recognize tomato (Solanum lycopersicum) and Arabidopsis MIR169 promoters using yeast one-hyb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Lastly, circRNAs are a class of endogenous ncRNAs characterized by covalently closed structures without 5′ or 3′ ends ( Bhogireddy et al., 2021 ). Rao et al. (2022b) investigated the tomato response to HS and they reported that plants improve their HS tolerance through Hsf-mediated transcriptional regulation of miR169s.…”
Section: Epigenetic Post-transcriptional and Post-translational Regul...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, circRNAs are a class of endogenous ncRNAs characterized by covalently closed structures without 5′ or 3′ ends ( Bhogireddy et al., 2021 ). Rao et al. (2022b) investigated the tomato response to HS and they reported that plants improve their HS tolerance through Hsf-mediated transcriptional regulation of miR169s.…”
Section: Epigenetic Post-transcriptional and Post-translational Regul...mentioning
confidence: 99%
“…Lastly, circRNAs are a class of endogenous ncRNAs characterized by covalently closed structures without 5′ or 3′ ends (Bhogireddy et al, 2021). Rao et al (2022b) investigated the tomato response to HS and they reported that plants improve their HS tolerance through Hsfmediated transcriptional regulation of miR169s. HsfA1a, HsfA2 and HsfA7a have a key role in HS response and they also bind to the promoters of miR169, leading to transcriptional enhancement of miR169s.…”
Section: Epigenetic Post-transcriptional and Post-translational Regul...mentioning
confidence: 99%
“…Low temperature will down-regulate the expression of miR164a/b-5p, release the inhibition of NAM3, and improve the cold tolerance of tomato ( Dong et al., 2022 ). High temperature upregulates the expression of miR319d and miR169, and inhibiting the transcription of downstream target genes to improve tomato heat tolerance ( Shi et al., 2019 ; Rao et al., 2022 ). However, the target genes of miR319d at high temperature are unknown.…”
Section: The Role Of Mirnas In Abiotic Stresses In Tomatomentioning
confidence: 99%
“…Besides this miRNA, miR169 also appears to be involved in heat tolerance regulatory network in tomato. Over-expression of miR169 can significantly inhibit the expression of its target gene NF-YA9/10, and result in the markedly increased activity of its downstream ascorbate peroxidase (APX) (H 2 O 2 scavenging enzyme), then improved tomato heat tolerance ( Rao et al., 2020 ; Rao et al., 2022 ). In addition, miR167a acts as a responsive medium under a variety of abiotic stresses.…”
Section: The Role Of Mirnas In Abiotic Stresses In Tomatomentioning
confidence: 99%
“…In recent years, the regulation mechanism of miRNAs in the abiotic response has been discovered in some plants. In Arabidopsis and tomato, the HSF transcription factor is involved in heat stress tolerance through binding to the MIR169 promoter to positively regulate the transcription of MIR169 and negatively regulate the expression of its target gene NF-YA9/10 [ 61 ]. The SERRATE protein, a conserved RNA processing factor in eukaryotes, encodes a C2H2 zinc finger protein.…”
Section: Mechanisms Of Mirna Transcriptional Regulationmentioning
confidence: 99%